Apoqnmatulti’k: Turning the Tide for Collaborative Research - Denny, Shelley; Jeddore, Skyler; Borland, Meghan; Iverson, Sara; Whoriskey, Fred; Stokesbury, Mike; Syliboy, Alanna; VanderKloet, Evelien; Porter, Darren; Bailey, Megan; Sutherland, Maggie; Bradford, Rod (Journal of Aboriginal Economic Development, 2025)
A collaborative and holistic approach is essential to achieving a healthy and resilient aquatic ecosystem. Apoqnmatulti’k (Mi’kmaw for “we help each other”) is a partnership that involves the Unama’ki Institute of Natural Resources, the Confederacy of Mainland Mi’kmaq, commercial fisher Darren Porter, the Ocean Tracking Network, Acadia University, Dalhousie University, and Fisheries and Oceans Canada-Science. Apoqnmatulti’k is founded on the shared participation of Mi’kmaw, local, and Western scientific knowledge holders, aiming to better understand valued aquatic species in Pitu’pa’q (Bras d’Or Lake) and Pekwitapa’qek (Minas Basin). Guided by the principle of Etuaptmumk (Two-Eyed Seeing), Apoqnmatulti’k serves as a model for how the incorporation of diverse perspectives can enhance knowledge, ensure transparency and accessibility of information, and transform fisheries management and conservation. This paper focuses on the challenges, lessons learned, and achievements derived from collaboration and the development of a strong partnership.